2017
DOI: 10.1016/j.tjog.2016.12.018
|View full text |Cite
|
Sign up to set email alerts
|

The effect of oxytocin and Kisspeptin-10 in ovary and uterus of ischemia-reperfusion injured rats

Abstract: The present results suggest that exogenous application of oxytocin and kisspeptin can have antioxidant effects on the uterus and ovary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 18 publications
3
32
0
1
Order By: Relevance
“…In this study, we showed that prolonged hypoxia clearly damaged the endometrial and myometrial cells and these degenerative changes did not improve during the recovery period even after leaving the tissue in 100% oxygen for a long period, suggesting that irreversible damage to some uterine compartments took place. Our findings are consistent with previous studies in vivo which found severe degenerative endometrial changes with infiltration of leukocytes (including eosinophils) after prolonged ischemia in nonpregnant rats (Sahin et al 2014;Aslan et al 2017). Activated eosinophils were reported to release free radicals (Chanez et al 1990) and were implicated in epithelial damage (Yukawa et al 1990).…”
Section: Discussionsupporting
confidence: 93%
“…In this study, we showed that prolonged hypoxia clearly damaged the endometrial and myometrial cells and these degenerative changes did not improve during the recovery period even after leaving the tissue in 100% oxygen for a long period, suggesting that irreversible damage to some uterine compartments took place. Our findings are consistent with previous studies in vivo which found severe degenerative endometrial changes with infiltration of leukocytes (including eosinophils) after prolonged ischemia in nonpregnant rats (Sahin et al 2014;Aslan et al 2017). Activated eosinophils were reported to release free radicals (Chanez et al 1990) and were implicated in epithelial damage (Yukawa et al 1990).…”
Section: Discussionsupporting
confidence: 93%
“…Studies have been conducted on the effects of kisspeptin on the HPG axis and reproductive system in recent years (Dhillo et al., ; George et al., ; Kuohung & Kaiser, ). In recent years, studies have been carried out to determine whether this peptide has an antioxidant effect (Akkaya et al., ; Aslan et al., ; Aydin et al., ; Milton et al., ). A study by Akkaya, Eyuboglu, Erkanlı Senturk, and Yilmaz () on the testicular tissue has suggested that kisspeptin may reduce lipid peroxidation and may have antioxidant effects.…”
Section: Discussionmentioning
confidence: 99%
“…The decreased release of LH and FSH in hypothalamic dysfunction results in oxidative stress (Hurtado de Catalfo, Ranieri‐Casilla, Marra, De Alaniz, & Marra, ; Muthuvel et al., ). Recent studies have shown that kisspeptin protects against oxidative damage (Akkaya, Kilic, Dinc, & Yilmaz, ; Aslan, Erkanli Senturk, Akkaya, Sahin, & Yılmaz, ; Aydin, Oktar, Yonden, Ozturk, & Yilmaz, ; Milton, Chilumuri, Rocha‐Ferreira, Nercessian, & Ashioti, ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the protective contribution of OT aganist ischemia/reperfusion (I/R) injury has been demonstrated in the heart (11,12), ovary and uterus (9) and kidney and liver (10).…”
Section: Introductionmentioning
confidence: 99%